Contraceptive practice among married women of reproductive age group in rural Telangana: a cross sectional study - Salgar, A. H.; Bhargavi, A. N.; Nagaiah, G. (International Journal Of Community Medicine And Public Health, 2020)
Background: Contraceptive practice in India is known to be very heavily skewed towards terminal methods which mean that contraception in India is practiced primarily for birth limitation rather than birth planning. The objective of the study was to study contraceptive practice among married women of reproductive age in rural area. Methods: The study was a cross sectional study among married women with reproductive age group in rural areas of Sangareddy district carried out in Department of Community Medicine, MNR Medical College, Sangareddy, during November 2015 to February 2016. A total sample size of 113 women who are married in age group of 15-45 years and presumed to be sexually active were included in study. The data were collected using structured questionnaire and in-depth interview guide in local language. The collected data were analyzed with proper statistical methods using MS excel 2010. Results: Out of 113 women majority of women were in age group 20-29 years (52.21%). The utilization of contraceptive method was present in 52.21% women with oral contraceptive pills (23.89%) as a choice of method in majority of women. Conclusions: Hence, we conclude that still there is need to create awareness regarding importance of contraception among rural women.